Father’s Fear of Childbirth during Antenatal Period in Allied Hospitals of RMU, A Cross-Sectional Study - Saif, Sania; Iqbal, Umaima; Naeem, Shaiza; Tasleem, Ayesha; Maryam, Saba; Kalsoom, Afifa (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction The term "fathers’ fear of childbirth" refers to the unpleasant and apprehensive feelings that arise during the prenatal period and are mostly felt during labor. An estimated 13% of expecting men experience pathological dread during their pregnancy. Fathers’ anxiety about childbirth may be attributed to several factors such as having their first child, having their pregnant woman delivered via cesarean section, experiencing problems during labor, having a restricted income, and so on. The purpose of this study is to shed light on the men in our community who are afraid of giving birth. To foster better family dynamics, the ultimate objective is to de-stigmatize conversations on fathers’ emotional health and give priority to their mental health. Objectives This study aims to measure the fear of childbirth that dads have throughout the prenatal period at RMU’s affiliated hospitals and assess the relationship between fathers’ fear of childbearing in relation to lifestyle choices. Materials and Methods 190 dads participated in an observational cross-sectional study employing the dads’ Fear of Childbirth Scale (FFSC). The data was gathered using a self-administered questionnaire and consecutive sampling. The dread of childbirth among dads was analyzed statistically using Chi-square and Fisher Exact tests, as well as other tests, to find correlations with different demographic variables. Results According to the survey, 51.6% of fathers and 6.8% of fathers, respectively, report having moderate dread, while 41.6% report having mild fear. Fear and age (p=0.023), years of marriage (p=0.015), employment (p=0.022), and history of miscarriage (p=0.024) were shown to be significantly correlated. Conclusion In our research sample, moderate fear predominated, followed by mild and severe dread. "As the time of childbirth approaches, my worries increase" was the item with the highest mean and standard deviation among all FFCS items. The study finds a strong correlation between certain demographic characteristics (age, employment, history of miscarriage, and years of marriage) and fathers’ anxiety of delivery. Keywords Fathers’ fear, childbirth, antenatal.